2015
DOI: 10.1007/5584_2015_162
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Primary Cytomegalovirus or Epstein-Barr Virus Infection on the Course of Idiopathic Thrombocytopenic Purpura

Abstract: Idiopathic thrombocytopenic purpura (ITP) in children is usually triggered by a viral infections such as cytomegalovirus (CMV) or Epstein-Barr virus (EBV) infection. The aim of this study was to assess the frequency of CMV and EBV infections in children with first relapse of ITP, and the influence of these infections on the course and response to treatment of ITP. Sixty patients (30 boys and 30 girls) with ITP were enrolled into the study. We found that the age at the onset of ITP was from 1 month to 17 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 16 publications
(19 reference statements)
1
13
0
1
Order By: Relevance
“…Smalisz-Skrzypczyk et al also found no significant impact of CMV positivity on the clinical course or response to therapy. 17 Wu et al found no statistically significant difference between CMV positivity and platelet count. 32 Similarly, Elalfy et al did not find that CMV had any impact on the clinical severity of the disease but they suggested that the virus might play a role in duration of initial response to immunomodulation.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Smalisz-Skrzypczyk et al also found no significant impact of CMV positivity on the clinical course or response to therapy. 17 Wu et al found no statistically significant difference between CMV positivity and platelet count. 32 Similarly, Elalfy et al did not find that CMV had any impact on the clinical severity of the disease but they suggested that the virus might play a role in duration of initial response to immunomodulation.…”
Section: Discussionmentioning
confidence: 95%
“…A similar observation was also noted by Nishio et al 31 DiMaggio et al and Smalisz-Skrzypczyk et al reported that clinical manifestations of CMV infection in immunocompetent cases is often asymptomatic and usually noticed retrospectively. 15,17 On the other hand, Jin et al suggested that ITP patients may display CMV-like symptoms at the time of thrombocytopenia diagnosis when CMV infects megakaryocytes and causes direct cytotoxicity, whereas the symptoms may be displayed a few weeks before the diagnosis of thrombocytopenia when a CMVrelated secondary ITP is caused by an immunological reaction after a recent CMV infection. 13 Moreover, our results found that CMV did not have any impact on the clinical severity of the disease, outcomes of refractory cases or the response to treatment (►Tables 3-5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This protein is involved in the pathophysiological process of a variety of diseases such as cancer. Increased B cell activating factor causes decreased levels of platelet autoantibodies, which accelerates the blood platelet defect; iv) bone marrow megakaryocyte abnormity (11). Decreased amount of megakaryocytes affects normal platelet production, which is a major cause of several diseases; and v) Th1/Th2 dysfunction (12).…”
Section: Discussionmentioning
confidence: 99%
“…Incremental B cytokines lead to decreasing levels of platelet autoantibodies and accelerate thrombocytopenia. (IV) Abnormal expression of Bone marrow megakaryocyte [8]. The reduction of megakaryocytes affects the production of normal platelets.…”
Section: Introductionmentioning
confidence: 99%